BAHASA PENGHELA ILMU PENGETAHUAN DALAM PEMBELAJARAN BERBASIS TEKS: RANCANG BANGUN MATERI PEMBELAJARAN TEMATIK TERPADU - Mahsun, Mahsun; Wahidah, Baiq; Khotimah, Khusnul; Khairussibyan, Muh. (LPPM Universitas Mataram, 2020)
Based on the result of the researches onÃ‚Â text book materials under 2013 curriculum published byÃ‚Â the government, for elementary school level, it is found that the materials from one competence to another on those books are not well-integrated, even the competences are elaborated in single theme or subtheme. Though those text books are entitled Ã¢â‚¬Å“Integrated Thematic Book of Curriculum 2013Ã¢â‚¬Â, they still do not show the integration they should give. It is assumed that the disordered materials are caused by the absence of a certain field of knowledge that should be used as a binder and medium of transmitting and integrating the whole competences in case the material changes. Regarding the problem, this article delivers a brief description on how Indonesian language is used to bind and become a medium of transmission of the whole nonintegrated field of competences from any different materials. In other word, this article presents a conceptual model of designing integrated thematic learning on the basis of the language as a medium of transferring knowledge